Analisis Pengaruh Debt to Equity Ratio, Return On Equity, dan Total Asset Turnover Terhadap Price to Book Value (Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2017-2024) - kaylla salsabila; Devyanthi Syarif; Tjipto Sajekti (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This study aims to analyze the influence of Debt to Equity Ratio (DER), Return on Equity (ROE), and Total Asset Turnover (TATO) on Price to Book Value (PBV) in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2017–2024 period. The urgency of this research stems from growing global economic uncertainty and domestic financial market volatility, which have significantly impacted the valuation of the banking sector in Indonesia. The recent decline in PBV among major banks highlights the need to reassess which financial indicators are most influential in shaping investor perceptions. This research employs a quantitative approach using multiple linear regression analysis and classical assumption testing. Secondary data were obtained from audited annual financial reports, and analysis was conducted using SPSS version 26. The results show that ROE has a positive and significant effect on PBV, indicating that profitability plays a key role in enhancing firm valuation. Conversely, DER and TATO do not have a statistically significant impact on PBV. Simultaneously, DER, ROE, and TATO collectively do not significantly affect PBV at the 5% level, although ROE remains the most dominant factor. These findings suggest that in the banking sector, market valuation is more responsive to profitability metrics than to capital structure or asset efficiency. Therefore, banks are advised to focus on improving ROE as a strategic financial objective to increase firm value and attract investors in a competitive capital market environment.